Exploitation of Parthenium hysterophorous biomass as low-cost substrate for cellulase and xylanase production under solid-state fermentation using Talaromyces stipitatus MTCC 12687. Issue 4 (October 2018) - Bharti, Amit Kumar; Kumar, Amit; Kumar, Alok; Dutt, Dharm
Abstract: To make the enzyme production process appreciably inexpensive in respect of SSF, use of economical substrates is of great interest. Out of total eight employed solid substrate, Parthenium hysterophorous biomass exhibited its potential and displayed maximum endoglucanase (30 IU/gds), xylanase (582 IU/gds) and FPase (2.86 FPU/gds) activities. During optimization of cultural parameters, Talaromyces stipitatus MTCC 12687 produced maximum endoglucanase (53.3 IU/gds), FPase (4.51 FPU/gds) and β-glucosidase (62.6 IU/gds) at temperature (30 °C), incubation time (5 th day), pH (6.0) and moisture content (80%) with the supplementation of peptone as the nitrogen source and Tween-80 as the surfactant under SSF conditions. During the process of optimization different enzyme activities viz. endoglucanase, xylanase, FPase and β-glucosidase were enhanced by approximately 2.0, 1.54, 2.0 and 2.7 fold respectively compared to their respective controls. Talaromyces stipitatus MTCC 12687 enzymes hydrolysed untreated and organosolve pretreated P. hysterophorous biomass to release 93 ± 3.87 and734 ± 17 mg/g of reducing sugars respectively after hydrolysis time of 48 h.